Evaluating the effectiveness of GSU-based learning modules in improving the primary six students' understanding level in Geometry - Dhinapriya Balachandran, 1983-; Mohd. Salleh Abu, supervisor; Fakulti Pendidikan (2013)
Thesis (Sarjana Pendidikan (Matematik)) - Universiti Teknologi Malaysia, 2013